2013
DOI: 10.1002/cbdv.201300149
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Phenolic Compounds and Triterpenoids from the Galls of Terminalia chebula

Abstract: Nine phenolic compounds, including two phenolic carboxylic acids, 1 and 2, seven hydrolyzable tannins, 3-9, eight triterpenoids, including four oleanane-type triterpene acids, 10-13, and four of their glucosides, 14-17, isolated from a MeOH extract of the gall of Terminalia chebula Retz. (myrobalan tree; Combretaceae), were evaluated for their inhibitory activities against melanogenesis in B16 melanoma cells induced by α-melanocyte-stimulating hormone (α-MSH), against the Epstein-Barr virus early antigen (EBV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 58 publications
2
39
1
Order By: Relevance
“…The anti-inflammatory activity of these compounds has been demonstrated to be closely parallel with that of the inhibition of DMBA-TPA papilloma formation in the mouse-skin model (Yasukawa et al, 1996), and hence the oleanolic acid derivatives tested in this study might be expected to possess high antitumor-promoting effect in the same animal model. The high anti-inflammatory activities of various types of triterpene acids Banno et al, 2004Banno et al, , 2006Manosroi et al, 2013) and oleanane-type triterpene glycosides (Manosroi et al, 2013;Ukiya et al, 2006Ukiya et al, , 2007 have also been observed in our previous studies.…”
Section: Anti-inflammatory Activity Against Tpa-induced Inflammation mentioning
confidence: 50%
“…The anti-inflammatory activity of these compounds has been demonstrated to be closely parallel with that of the inhibition of DMBA-TPA papilloma formation in the mouse-skin model (Yasukawa et al, 1996), and hence the oleanolic acid derivatives tested in this study might be expected to possess high antitumor-promoting effect in the same animal model. The high anti-inflammatory activities of various types of triterpene acids Banno et al, 2004Banno et al, , 2006Manosroi et al, 2013) and oleanane-type triterpene glycosides (Manosroi et al, 2013;Ukiya et al, 2006Ukiya et al, , 2007 have also been observed in our previous studies.…”
Section: Anti-inflammatory Activity Against Tpa-induced Inflammation mentioning
confidence: 50%
“…Ellagitannins belong to a group of hydrolysable tannins and are polymers of hexahydroxydiphenolic acid, which is a dimeric form of gallic acid. It is believed that hydrolysable tannins including ellagitannins have antioxidant and anti-melanogenic activities, and the melanogenesis-inhibitory activity is due to the inhibition of the expression of MITF, followed by a decrease in the expression of tyrosinase and TRP-1 [17]. Therefore, the ellagitannins in berries may contribute to the reduction of pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The leaf gall of T. chebula are reported to be very rich in tannins, triterpenoids, flavonoids, essential oils, and others phenolic constituents. [5,7] It was reported that, phenolicsor tannins may interfere with energy generation of worms by uncoupling oxidative phosphorylation or they binds to the free protein of the gastrointestinal tract of the worms and lead to death.…”
Section: Resultsmentioning
confidence: 99%
“…5 Gall extracts of T. chebula have been found to possess anti-inflammatory activity, anti-bacterial, anti-tyrosinase activity, anti-cancer activity, and anti-ageing activity. 7 In this study, we have evaluated the anthelmintic potential of T. chebula leaf gall extracts and elucidate its phytochemical constituents for having knowledge on the principal components responsible for its biological activity.…”
Section: Introductionmentioning
confidence: 99%